Detection of Heavy Metal Pb in Cosmetics at Traditional Market of Banjarmasin: Deteksi Logam Berat Timbal (Pb) dalam Kosmetik yang Beredar di Pasar Tradisional Banjarmasin - Rahmadani; Alawiyah, Tuti; Herowati, Rina (Akademi Farmasi Surabaya, 2021)
Background: Impurities produced from the basic ingredients of making cosmetics, one of which is lead (Pb). Lead is a substance that is harmful and toxic to the human body. Lead can affect the hematopoetic system, nervous system, reproductive system, endocrine system and is carcinogenic. Objective: To determine the presence of lead (Pb) heavy metal contamination in mascara products circulating in the Banjarmasin traditional market. Methods: This study used a descriptive observational method. Testing qualitatively using KI, NaOH, and HCl reagents. Results: The test results obtained from the sample after being reacted with the three reagents showed a positive presence of lead (Pb) heavy metal. With KI solution shows a yellow-black precipitate, with NaOH solution shows a white precipitate and with HCl solution shows a white precipitate. Conclusion: Qualitative tests on mascara cosmetic products taken at different points of sale in the Banjarmasin traditional market using color reagents in KI solution, NaOH solution, and HCl solution, it can be concluded that the qualitative test results show a positive presence of heavy metal lead (Pb). on mascara products.